Ihtikar Dan Tas’ir Kajian Hukum Ekonomi Syariah - Sulthonuddin, Bung Hijaj; Haerudin, Usep Malik; Adawiyah, Nurul Robiatul (STAI Al-Musaddadiyah Garut, 2025)
This paper discusses the Law of Ihtikar and Tas'ir in trade and business activities, namely the hoarding of goods and pricing. Islam requires the implementation of moral values in all economic activities, so the issue of Ihtikar and Tas'ir is very important to be studied in Sharia Economic Law. The formulation of the problem is what is meant by Ihtikar, what is meant by Tas'ir, and how according to the view of sharia economic law. The method used in this writing is library research with a literature approach using existing books or references related to the topic of discussion. The result of his research is that the Ihtikar law is haram if the goods that are hoarded are urgently needed by the community, which results in an increase in prices. Furthermore, Islam allows the existence of Tas'ir to benchmark prices by intervening in economic activities by issuing several policies and rules that have an impact on prices for the benefit of the public. Keywords: Ihtikar, Tas'ir, Sharia Economic Law.